Authorisms words wrought by writers - Dickson, Paul (Bloomsbury, 2014)
"William Shakespeare's written vocabulary consisted of 17,245 words, including hundreds that were coined or popularized by him. Some of the words never went further than their appearance in his plays, but others...like bedazzled, hurry, critical, and anchovy...are essential parts of our standard vocabulary today. Many other famous and lesser-known writers have contributed to the popular lexicon. According to the Oxford English Dictionary, Sir Walter Scott ranks second to Shakespeare in first uses of words and giving a new and distinct meaning to already existing words (Free Lances for freelancers). John Milton minted such terms as earthshaking, lovelorn, by hook or crook, and all Hell broke loose, and was responsible for introducing some 630 words. Gifted lexicographer Paul Dickson deftly sorts through neologisms by Chaucer (a ha), Jane Austen (base ball), Louisa May Alcott (co-ed), Mark Twain (hard-boiled), Kurt Vonnegut (granfalloon), John le Carre (mole), William Gibson (cyberspace), and many others. Presenting stories behind each word and phrase, Dickson enriches our appreciation of the English language in a book as entertaining as it is enlightening"..
Includes bibliographical references and index
Keywords: LANGUAGE ARTS & DISCIPLINES / Linguistics / Historical & Comparative; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Linguistik; Literatur; Philosophie; Literature -- Philosophy; Lexicography in literature; Influence (Literary, artistic, etc.); Linguistics in literature; Englisch; Neologismus